2006
DOI: 10.1111/j.1440-1746.2006.04564.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of oxidative metabolites of bilirubin in subjects with Gilbert syndrome

Abstract: An inverse relationship was demonstrated between serum bilirubin level and urinary excretion of biopyrrins, which is presumably due to antioxidative effects of elevated serum bilirubin levels in Gilbert syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…This individual's records indicated that his serum bilirubin concentrations were at the upper limit of the accepted normal range (2.2-3 g/dl). Nevertheless, this level of plasma bilirubin concentrations corresponds closely to the mean value of 2.7 ± 1.0 observed in 33 Gilbert's syndrome patients versus normal values of 1.0 ± 0.3 in controls (Vitek et al, 2007). Gilbert's syndrome is associated with mutations in one or more genes coding for bilirubin UDP-glucuronyltransferase (UGT) (Teng et al, 2007).…”
Section: Discussionsupporting
confidence: 72%
“…This individual's records indicated that his serum bilirubin concentrations were at the upper limit of the accepted normal range (2.2-3 g/dl). Nevertheless, this level of plasma bilirubin concentrations corresponds closely to the mean value of 2.7 ± 1.0 observed in 33 Gilbert's syndrome patients versus normal values of 1.0 ± 0.3 in controls (Vitek et al, 2007). Gilbert's syndrome is associated with mutations in one or more genes coding for bilirubin UDP-glucuronyltransferase (UGT) (Teng et al, 2007).…”
Section: Discussionsupporting
confidence: 72%
“…Bilirubin has also been shown to significantly interfere with the complement system, with all of the possible protective consequences (reviewed in Basiglio et al, 2010). Consistent with this data, several studies have demonstrated a negative relationship between serum bilirubin and C-reactive protein levels (Vítek et al, 2007a; Hwang et al, 2011; Yoshino et al, 2011). In addition, the modulatory effects of bilirubin on T regulatory cell differentiation were recently reported (Rocuts et al, 2010), further underlining the protective role of bilirubin in the pathogenesis of chronic inflammatory as well as in autoimmune conditions.…”
Section: Biological Properties Of Bilirubinsupporting
confidence: 75%
“…18 Vítek et al demonstrated an inverse relationship between serum bilirubin level and urinary excretion of biopyrrins and suggested antioxidative effects of elevated serum bilirubin levels in Gilbert syndrome. 19 Yamamoto et al studied the dynamics of oxidative stress after myocardial ischemia reperfusion in rat models using urinary excretion of biopyrrins and their generation in various organs as oxidative stress markers and suggested that urinary excretion of biopyrrins can serve as a useful marker of systemic oxidative stress after myocardial ischemia -reperfusion. 20 Ueyama et al reported that cardiac and aortic macrophages upregulate HO-1 in response to emotional stress and catecholamine surges as an endogenous defense mechanism against oxidative stress in rat models of takotsubo cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%